2018
DOI: 10.1089/ham.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Alpha-1-Acid Glycoprotein Is a Sensitive Marker of Glomerular Protein Leakage at Altitude

Abstract: Talks, Ben J., Susie B. Bradwell, John Delamere, Will Rayner, Alex Clarke, Chris T. Lewis, Owen D. Thomas, and Arthur R. Bradwell. Urinary alpha-1-acid glycoprotein is a sensitive marker of glomerular protein leakage at altitude. High Alt Med Biol. 19:295–298, 2018.—Proteinuria is an established feature of ascent to altitude and may be caused by a loss of negative charges on glomerular capillary walls (GCWs). To test this hypothesis, we measured two similar sized but oppositely charged proteins in urine: negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
2
11
0
Order By: Relevance
“…In addition, we also tried to measure ORM in urine (unpublished results). Our study showed the evaluation of ORM in urine of patients with DM and DR might be important, which agrees with results of other laboratories (Christiansen et al, 2010;KUstan et al, 2016;Talks et al, 2018). In all of our patients, we found significant increase of ORM levels when compared to normal population of the same age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we also tried to measure ORM in urine (unpublished results). Our study showed the evaluation of ORM in urine of patients with DM and DR might be important, which agrees with results of other laboratories (Christiansen et al, 2010;KUstan et al, 2016;Talks et al, 2018). In all of our patients, we found significant increase of ORM levels when compared to normal population of the same age.…”
Section: Discussionsupporting
confidence: 92%
“…ORM is considered to be proof of association between obesity and periodontitis (Range et al, 2013). Interesting studies measuring ORM in urine of patients with DM1 might be used in induction risk evaluation with urinary tract problems concerning DR patients (Christiansen et al, 2010;Kustan et al, 2016;Talks et al, 2018). Lately, increased attention is focused on evaluation of ORM I and II subclasses.…”
Section: Introductionmentioning
confidence: 99%
“…All samples were thawed at room temperature for 1 hour before analysis. The 24-hour urine samples were first analysed for α1-AGP using radial immunodiffusion (RID; Talks et al, 2018)7 and the results were converted to excretion rates (mg/24 hours or μg/min). A subset of samples (119 out of 201) were then analysed using a latex-enhanced immunoassay on the Optilite turbidimetric analyser (The Binding Site, Birmingham, UK; online supplementary appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Proteinuria typically results from protein leakage from the capillary lumen through the glomerular filter,1 with some removal in the tubules, as shown by studies inhibiting renal tubular reabsorption with lysine infusions 2. Comparisons between albumin, a selectively reabsorbed,3 66 kDa, negatively charged (pI 4.7) protein that passes through the glomerular membrane via the slit diaphragm pores,4 and alpha-1 acid glycoprotein (α1-AGP),5–7 a smaller (41–43 kDa) and more negatively charged protein (pI 2.7)5 7 indicate that urinary α1-AGP is a more sensitive marker of glomerular leakage than albumin 7–9. Urinary α1-AGP excretion has implicated the glomerular origin of the proteinuria exhibited with both, altitude7 and post-exercise 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation